PENERAPAN PRAKTIK MONOPOLI PENGUASAAN SUMBER DAYA ALAM OLEH BADAN USAHA MILIK NEGARA (BUMN) MENURUT UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT (Studi Kasus Pada PT PLN) - Reza Muhammad Noor (Program Magister Ilmu Hukum Universitas Pancasila, 2019)
The State have rights and power to monopolize economic activity that solely do for national interests, either to create the prosperity of its people economically or to seize strategic benefit to the State that contained in Article 51 Prohibition of Monopoly Practices and Unhealthy Business Competition Acts Number 5 of 1999. The concern of this thesis is about the implementation of Pancasila Economic System concept in Indonesia, the position of PT PLN (Persero) to implements monopolistic practices related to Article 51 Prohibition of Monopoly Practices and Unhealthy Business Competition Acts Number 5 of 1999, it’s overcome the obstacles towards monopoly practices exclusion for PT PLN (Persero) as StateOwned Enterprise that used for the most prosperous of the people.